The Preparation of Academics for Teaching Classes - Possibilities of Support and Examples of Good Practice - Sajdak, Anna (Studia Oeconomica Posnaniensia, 2015)
In this paper, the author addresses the issues of imperfections related to the systemic preparation of academics for teaching classes as well as fostering the development of academics as educators. Some higher education institutions have introduced obligatory teaching courses designed for novice staff, others have opted for voluntary participation in various forms of training, while a substantial number of institutions are still facing a dilemma as to the form of support to be organized. When designing a programme of activities, it may be advisable to explore some previously tested solutions which represent so-called "good practice". The paper presents certain proposals which are the result of the author’s in-depth studies on the theory and practice of academic teaching in Poland and Germany. The solutions described in the article are not specific to any given type of higher education institution. Academic teaching centres in Germany have been developed equally in technical, economic and traditional universities. Their activities are based on the achievements of interdisciplinary teams of academics; including pedagogues, psychologists, teachers of specific disciplines, and specialists in systemic solutions introduced at a given university (including distance teaching specialists and IT specialists). The article will present solutions located mainly within the constructivist (workshops, seminars, training sessions) and humanistic (co-teaching, coaching, supervision, supervisory groups) paradigms.